Models of Ecumenical Dialogue in the Discourse of the Russian Orthodox Church of the Moscow Patriarchate - L. A. Gorodilova (Концепт: философия, религия, культура, 2022)
The article is devoted to the models of ecumenical dialogue in the Russian context on the example of the Russian Orthodox Church of the Moscow Patriarchate. The wide-spread and flourishing discussions about ecumenism in the religious studies and theological fields constitute the problem of this study. The author investigates the problem with the aim to identify existing models of an ecumenical dialogue. Following from this purpose the most significant and discussed concepts of ecumenical dialogue in Russia are noted. The emphasis is placed on the widespread concept of two ecumenisms, most fully disclosed by A. V. Shishkov, and related discussions in the scientific and theological fields. Also, a discussion in the church discourse was revealed, which is based on the concepts of representatives of the Russian Orthodox Church: prot. M. Kozlov, mitr. Hilarion (Alfeyev), fr. Georges Florovsky, archm. Sophronia (Sakharova) and others. To outline the broad picture, there was established the position of the Roman Catholic Church as well as its messages addressed to Orthodoxy. In addition, three main trends in the Russian Orthodox Church in relation to ecumenism are identified and described. The first is anti-ecumenism, its members are against any dialogue with non-Orthodoxy. The second is moderate ecumenism, where participants advocate the idea of acceptable and unacceptable forms of ecumenism without making edits to the Church doctrine, and the third are modernist ecumenists who are ready for changes in the teaching of the Church for the sake of the dialogue. Then, there was a transition to the term ecumenism in the context of modern conceptions about the phenomenon and also in the context of the history of the ecumenical movement of the 20th century. The author makes a conclusion about a fundamental importance of the idea of the unity of Christians for the identification of models of ecumenical dialogue. The unity can be determined as unity in one Church, as well as unity within a common space of communication without crossing borders and making one united church. It is noted that the existing concepts and terminology do not reflect this aspect, thus the author suggests the possibility of using such terms as adaptive and integrative dialogue, and lays out prospects for solving the problem.